2004
DOI: 10.1002/hipo.10194
|View full text |Cite
|
Sign up to set email alerts
|

Functional differentiation within the medial temporal lobe in the rat

Abstract: The structures that comprise the medial temporal lobe (MTL) have been implicated in learning and memory. The question of primary concern in the present research was whether the group of anatomically related structures (hippocampus, subiculum, presubiculum/parasubiculum, entorhinal cortex, perirhinal/postrhinal cortex) are involved in mediating a similar memory process or whether the individual structures are differentially involved in memory processes and/or in handling various types of information. A series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 70 publications
7
40
1
Order By: Relevance
“…The evidence now suggests that this PR function can subserve both defensive conditioning (Fig. 6 B) (Bucci et al, 2000) and working memory (Young et al, 1997;Murray and Richmond, 2001;Jarrard et al, 2004).…”
Section: Neurophysiological Basis Of the Cs-dependent Pr Requirementmentioning
confidence: 85%
See 3 more Smart Citations
“…The evidence now suggests that this PR function can subserve both defensive conditioning (Fig. 6 B) (Bucci et al, 2000) and working memory (Young et al, 1997;Murray and Richmond, 2001;Jarrard et al, 2004).…”
Section: Neurophysiological Basis Of the Cs-dependent Pr Requirementmentioning
confidence: 85%
“…All surgical procedures were performed under aseptic conditions. Aspiration PR lesions were used because we found this permits more complete and selective damage than neurotoxin lesions (Jarrard et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies report impairment on the water maze task (Kaut and Bunsey, 2001;Liu and Bilkey, 2001) and others do not (Bussey et al, 1999;Mumby and Glenn, 2000). A radial maze study suggested that impairment associated with perirhinal-postrhinal damage might depend more on the type of memory tested than on the spatial requirements of the task (Jarrard et al, 2004).…”
Section: Introductionmentioning
confidence: 99%